Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Guanosine Promotes Proliferation in Neural Stem Cells from Hippocampus and Neurogenesis in Adult Mice - Tetsade C. B. Piermartiri; Beatriz dos Santos; Fernanda G. Q. Barros-Aragão; Rui D. Prediger; Carla Inês Tasca (Molecular Neurobiology, 2020)

Treadmill Exercise Attenuates l-DOPA-Induced Dyskinesia and Increases Striatal Levels of Glial Cell-Derived Neurotrophic Factor (GDNF) in Hemiparkinsonian Mice - Ana E. Speck; Marissa G. Schamne; Aderbal S. Aguiar; Rodrigo A. Cunha; Rui D. Prediger (Molecular Neurobiology, 2019)

Atorvastatin Prevents Early Oxidative Events and Modulates Inflammatory Mediators in the Striatum Following Intranasal 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Administration in Rats - Naiani F. Marques; Adalberto A. Castro; Gianni Mancini; Fernanda L. Rocha; Adair R. S. Santos; Rui D. Prediger; Andreza Fabro De Bem; Carla I. Tasca (Neurotoxicity Research, 2018)

Guanosine Prevents Anhedonic-Like Behavior and Impairment in Hippocampal Glutamate Transport Following Amyloid-β1–40 Administration in Mice - Débora Lanznaster; Josiel M. Mack; Victor Coelho; Marcelo Ganzella; Roberto F. Almeida; Tharine Dal-Cim; Gisele Hansel; Eduardo R. Zimmer; Diogo O. Souza; Rui D. Prediger; Carla I. Tasca (Molecular Neurobiology, 2017)

Temporal Dissociation of Striatum and Prefrontal Cortex Uncouples Anhedonia and Defense Behaviors Relevant to Depression in 6-OHDA-Lesioned Rats - Filipe C. Matheus; Daniel Rial; Joana I. Real; Cristina Lemos; Reinaldo N. Takahashi; Leandro J. Bertoglio; Rodrigo A. Cunha; Rui D. Prediger (Molecular Neurobiology, 2016)

CX3CR1 Disruption Differentially Influences Dopaminergic Neuron Degeneration in Parkinsonian Mice Depending on the Neurotoxin and Route of Administration - Fabrine Sales Massafera Tristão; Márcio Lazzarini; Sabine Martin; Majid Amar; Walter Stühmer; Frank Kirchhoff; Lucas Araújo Caldi Gomes; Laurance Lanfumey; Rui D. Prediger; Julia E. Sepulveda; Elaine A. Del-Bel; Rita Raisman-Vozari (Neurotoxicity Research, 2016)

Exercise Improves Cognitive Impairment and Dopamine Metabolism in MPTP-Treated Mice - Aderbal S. Aguiar; Samantha C. Lopes; Fabrine S. M. Tristão; Daniel Rial; Gisele de Oliveira; Cláudio da Cunha; Rita Raisman-Vozari; Rui D. Prediger (Neurotoxicity Research, 2016)

A Single Neurotoxic Dose of Methamphetamine Induces a Long-Lasting Depressive-Like Behaviour in Mice - Carlos D. Silva; Ana F. Neves; Ana I. Dias; Hugo J. Freitas; Sheena M. Mendes; Inês Pita; Sofia D. Viana; Paulo A. de Oliveira; Rodrigo A. Cunha; Carlos A. Fontes Ribeiro; Rui D. Prediger; Frederico C. Pereira (Neurotoxicity Research, 2014)

Six Weeks of Voluntary Exercise don’t Protect C57BL/6 Mice Against Neurotoxicity of MPTP and MPP+ - Aderbal S. Aguiar; Fabrine Sales Massafera Tristão; Majid Amar; Caroline Chevarin; Viviane Glaser; Roberta de Paula Martins; Eduardo Luiz Gasnhar Moreira; Raymond Mongeau; Laurence Lanfumey; Rita Raisman-Vozari; Alexandra Latini; Rui D. S. Prediger (Neurotoxicity Research, 2014)

Evaluation of Nigrostriatal Neurodegeneration and Neuroinflammation Following Repeated Intranasal 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP) Administration in Mice, an Experimental Model of Parkinson’s Disease - Fabrine S. M. Tristão; Majid Amar; Ines Latrous; Elaine A. Del-Bel; Rui D. Prediger; Rita Raisman-Vozari (Neurotoxicity Research, 2014)

Parkin-Knockout Mice did not Display Increased Vulnerability to Intranasal Administration of 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) - Aderbal S. Aguiar; Fabrine S. M. Tristão; Majid Amar; Caroline Chevarin; Laurence Lanfumey; Raymond Mongeau; Olga Corti; Rui D. Prediger; Rita Raisman-Vozari (Neurotoxicity Research, 2013)

Manganese-exposed developing rats display motor deficits and striatal oxidative stress that are reversed by Trolox - Fabiano M. Cordova; Aderbal S. Aguiar; Tanara V. Peres; Mark W. Lopes; Filipe M. Gonçalves; Daniela Z. Pedro; Samantha C. Lopes; Célso Pilati; Rui D. S. Prediger; Marcelo Farina; Keith M. Erikson; Michael Aschner; et al. (Archives of Toxicology, 2013)

Intranasal Administration of Neurotoxicants in Animals: Support for the Olfactory Vector Hypothesis of Parkinson’s Disease - Rui D. S. Prediger; Aderbal S. Aguiar; Filipe C. Matheus; Roger Walz; Layal Antoury; Rita Raisman-Vozari; Richard L. Doty (Neurotoxicity Research, 2012)

Single Intranasal Administration of 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine in C57BL/6 Mice Models Early Preclinical Phase of Parkinson’s Disease - Rui D. S. Prediger; Aderbal S. Aguiar; Argelia Esperanza Rojas-Mayorquin; Claudia P. Figueiredo; Filipe C. Matheus; Laure Ginestet; Caroline Chevarin; Elaine Del Bel; Raymond Mongeau; Michel Hamon; Laurence Lanfumey; Rita Raisman-Vozari (Neurotoxicity Research, 2010)

The cannabinoid receptor agonist WIN 55,212-2 facilitates the extinction of contextual fear memory and spatial memory in rats - Fabrício A. Pamplona; Rui D. S. Prediger; Pablo Pandolfo; Reinaldo N. Takahashi (Psychopharmacology, 2006)

Blockade of adenosine and dopamine receptors inhibits the development of rapid tolerance to ethanol in mice - Luciano C. Batista; Rui D. S. Prediger; Gina S. Morato; Reinaldo N. Takahashi (Psychopharmacology, 2005)